PERTUMBUHAN DAN PRODUKSI BERBAGAI VARIETAS KEDELAI (Glycine max L.) DI LAHAN SAWAH TADAH HUJAN - Suharno - (Teknosains, 2011)
One of the success in cultivation ofsoybean is determined by the seed. In Sawahan, Bleberan, Playen, Gunung Kidul, it had been observed at eight varieties ofsoybean. Those are five good national varietions Galunggung (V 1), varietions Wilis (V 2), varietions Mahameru (V3), varietions Malabar (V4) and varietions Bromo (V5) and three good local varieties varietions Local Imogiri (V 6), varietions Local Prambanan (V 7), and varietions Local Playen (V8). The observation was done in November 2007 untail February 2008, its purpose is to know which varieties indicating the good soybean growth and product. The experiment used Randomized Complete Block Design with one factor and 3 replacations. The data is group into two kinds. Those are the growth consisting the number of branch, leaves, and the height and the product the consist ofthe number ofpod, seed, and the weight of 100 soybean seeds. The results showed that application it concludes that good person grows bean it is variation Imogiri (V6), and the good bean of the production is varietion Imogiri (V6). Examinations use to factor of one it concludes that goodperson grows bean it is varietion and the good bean ofthe production is varietion local Imogiri. Key words: soybean variety, growth, produced.